Geochemical evidence for active tropical serpentinization in the Santa Elena Ophiolite, Costa Rica: An analog of a humid early Earth?. (14th May 2014) - Sánchez‐Murillo, Ricardo; Gazel, Esteban; Schwarzenbach, Esther M.; Crespo‐Medina, Melitza; Schrenk, Matthew O.; Boll, Jan; Gill, Ben C.
Abstract Serpentinization is a planetary process that has important consequences on geochemical cycles, supporting microbial activity through the formation of H2 and CH4 and having the potential to sequester atmospheric CO2. We present geochemical evidence of active serpentinization in the Santa Elena Ophiolite, Costa Rica which is sustained by peridotites with a degree of serpentinization less than 50% with no evidence of an internal heat source. Average spring water temperatures are 29.1°C. Two hyperalkaline spring systems were discovered, with a spring fluid pH up to 11.18. The fluids are characterized by low Mg (1.0–5.9 mg/L) and K (1.0–5.5 mg/L) and relative high Ca (29–167 mg/L), Na (16–27 mg/L), Cl (26–29 mg/L), hydroxide (41–63 mg/L), and carbonate (31–49 mg/L). Active CH4 (24.3% v/v) vents coupled with carbonate deposits ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghmgm1th2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />δ13CCO2 =−27 to −14‰</alternatives>; <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghmgm1tf1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />δ18OCO2 =−17 to − 6‰</alternatives>) also provide evidence for active serpentinization and carbonation. Isotope ratios of the alkaline fluids (δ18O = −7.9‰, δ2H = −51.4‰) and groundwater (δ18O = −7.6‰; δ2H = −48.0‰) suggests that, during base flow recession, springs are fed by groundwater circulation. Methanogenic Archaea, which comprises a relatively high percentage of the 16S rRNA gene tag sequences, suggests that biological methanogenesis may play a significant role in the system. Santa Elena's extreme varying weather results in a scenario that could be of significant importance for (a) improving the knowledge of conditions on a humid early Earth or Mars that had periodic changes in water supply, (b) revealing new insights on serpentinizing solute transport, and (c) modeling hydrogeochemical responses as a function of recharge.